2014
DOI: 10.1021/ic402867x
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Chiral Metal–Organic Frameworks via a Prochirality Synthetic Strategy with Achiral Ligands Step-by-Step

Abstract: Although some achievements of constructing chiral metal-organic frameworks (MOFs) with diverse achiral ligands have been made, there is still a lack of full understanding of the origin and formation mechanism of chirality, as well as the reasonable principles for the design and construction of chiral frameworks. The concept of prochirality in organic molecules and complex systems inspires us to explore the synthetic strategy of chiral MOFs based on achiral sources. Here, an achiral compound [Cu(en)][(VO3)2] (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…35−39 Template-controlled MOF synthesis has been well studied and reviewed extensively. 40−45 In the synthesis of anionic MOFs, N-centered cations (ammonium ions) are often the template of choice, since they are chemically robust, are easily synthesized, 46−48 have the potential to be chiral, 49 can be strong hydrogen bond donors. Given the potential for diverse impacts of such cations on MOF synthesis, we hypothesized that a series of unique frameworks could be synthesized from the same starting inorganic and organic building blocks in which the structural outcome was controlled by changing the templating cation.…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…35−39 Template-controlled MOF synthesis has been well studied and reviewed extensively. 40−45 In the synthesis of anionic MOFs, N-centered cations (ammonium ions) are often the template of choice, since they are chemically robust, are easily synthesized, 46−48 have the potential to be chiral, 49 can be strong hydrogen bond donors. Given the potential for diverse impacts of such cations on MOF synthesis, we hypothesized that a series of unique frameworks could be synthesized from the same starting inorganic and organic building blocks in which the structural outcome was controlled by changing the templating cation.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Since the [In­(O 2 CR) 4 ] − SBU is anionic, it is associated with charge-balancing cations deposited during the synthesis process, which are often themselves products of solvent decomposition. The role of such cations during MOF formation is not yet fully understood, but it is known that the type of cation can have a significant impact on pore architecture and diversity, leading to a potential template effect. Template-controlled MOF synthesis has been well studied and reviewed extensively. In the synthesis of anionic MOFs, N -centered cations (ammonium ions) are often the template of choice, since they are chemically robust, are easily synthesized, have the potential to be chiral, and can be strong hydrogen bond donors. Given the potential for diverse impacts of such cations on MOF synthesis, we hypothesized that a series of unique frameworks could be synthesized from the same starting inorganic and organic building blocks in which the structural outcome was controlled by changing the templating cation.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk chirality can be created in MOFs which exhibit a network topology that is inherently chiral because of the spatial organization of achiral building blocks. 32 But unfortunately, spontaneous resolution sometimes leads to the formation of racemic mixtures or conglomerates. 33 In the present work two compounds were crystallized with a chiral space group containing a 2 1 screw axis and they are optically inactive.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally, CCPs could be obtained by introducing certain chiral agents to play as components, counterions, templates, or structural directing agents. The limited species of commercial chiral agents and their high cost have hindered the development of CCPs. On the other hand, people have found that CCPs could also be prepared by adopting normal achiral starting materials, without any chiral agents (named a CCPs in the following discussion). This phenomenon is usually called “spontaneous resolution”. However, the products of those a CCPs were always racemic mixture (conglomerates) or racemic solid solution, which makes the study of application difficult.…”
Section: Introductionmentioning
confidence: 99%